Implementing enterprise risk management case studies and best practices - Fraser, John R. S. 1946-; Simkins, Betty J.; Narvaez, Kristina (Wiley, 2015)
Overcome ERM implementation challenges by taking cues from leading global organizations Implementing Enterprise Risk Management is a practical guide to establishing an effective ERM system by applying best practices at a granular level. Case studies of leading organizations including Mars, Statoil, LEGO, British Columbia Lottery Corporation, and Astro illustrate the real-world implementation of ERM on a macro level, while also addressing how ERM informs the response to specific incidents. Readers will learn how top companies are effectively constructing ERM systems to positively drive financ.
Includes bibliographical references at the end of each chapters and index. - Online resource; title from PDF title page (ebrary, viewed October 24, 2014)
Keywords: Insurance -- Case studies; Risk management -- Case studies; Assurance; Études de cas; Gestion du risque; Études de cas; BUSINESS & ECONOMICS; Insurance; Risk Assessment & Management; Insurance; Risk management; Unternehmen; Risikomanagement; Strategische Planung; Case studies